Parallel contextual array insertion deletion P systems and Siromoney matrix grammars. Issue 4 (4th July 2021) - Immanuel, S. James; Jayasankar, S.; Gnanaraj Thomas, D.; Paramasivan, Meenakshi; Thamburaj, Robinson; Nagar, Atulya K.
Abstract : James et al. have introduced a variant of P systems called parallel contextual array insertion deletion P system and studied some of its properties. The family of array languages generated by this variant of PCAIDPS includes families of array languages like recognisable picture languages (REC) and context-sensitive matrix languages L ( C S M G ) . In this paper we show that another interesting family L ( C F : R I R ) of Siromoney matrix languages is included in the family of array languages generated by PCAIDPS with two membranes. GRAPHICAL ABSTRACT: